Oxytocin blurs the self‐other distinction during trait judgments and reduces medial prefrontal cortex responses - Zhao, Weihua (Hum Brain Mapp, 2016)
The neuropeptide oxytocin (OXT) may act either to increase or blur the distinction between self and other and thereby promote either more selfish or altruistic behaviors. To attempt to distinguish between these two possibilities we performed a double‐blind, between‐subject, placebo‐controlled design study to investigate the effect of intranasal OXT on self and other (mother, classmate, or stranger) trait judgments in conjunction with functional magnetic resonance imaging. Results showed that OXT reduced response times for making both self and other judgments, but also reduced the accuracy of their subsequent recall, thereby abolishing the normal self‐bias observed in this task. OXT also abolished the positive correlation between response and self‐esteem scale scores seen in the PLC group, suggesting that its effects were strongest in individuals with higher levels of self‐esteem. A whole‐brain functional magnetic resonance imaging analysis revealed that OXT also reduced responses during both self and other trait judgments in the dorsal (dmPFC) and ventral (vmPFC) medial prefrontal cortex. A subsequent region of interest analysis revealed that behavioral performance and self‐esteem scale scores were associated with dmPFC activation and its functional connectivity with the anterior cingulate and between the vmPFC and posterior cingulate. Thus overall, while OXT may improve speed of decision making in self ‐vs. other trait judgments it also blunts the normal bias towards remembering self‐attributes and reduces mPFC responses and connectivity with other cortical midline regions involved in self‐processing. This is consistent with the view that OXT can reduce self‐centered behavior. Hum Brain Mapp 37:2512–2527, 2016. © 2016 Wiley Periodicals, Inc.